IMPLEMENTASI STRATEGI PEMBELAJARAN DENGAN PENDEKATAN INDEX CARD MATCH DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTS NEGERI 2 SLEMAN - Nur Zaytun Hasanah; Nurafni (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
In some units of educational institutions, there are still use monotonous learning strategies, the teacher lecturing and students listening, it has an impact on students who are not enthusiastic about participating in the class. The index card match strategy is not implemented in all educational units, due to the lack of teachers in applying this method in classroom learning. This method can overcome the problems that exist in the field related to the learning process. The purpose of this study is to interpret the implementation of learning strategies with the index card match to increase student motivation at MTS N 2 Sleman. This research is qualitative. Data collection techniques used are observation methods, documentation methods, and interview methods. The data analysis technique used is Miles, Huberman, and Saldana with the stages of data collection, data condensation, data presentation, and concluding. The results showed that the implementation of the learning strategy with the index card match approach was successful and successful in increasing students learning motivation at MTS N 2 Sleman. Therefore, the index card match strategy will provide new nuance for education, especially in the learning process. Learning with this strategy will make the learning atmosphere more fun and not boring.